Writing History in Macaulay’s Shadow: J.R. Seeley, E.A. Freeman, and the Audience for Scientific History in Late Victorian Britain - Hesketh, Ian (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2011)
So similar were the historical mindsets of J. R. Seeley and E. A. Freeman that there is still some confusion about which one coined the famous dictum that “history is past politics, politics present history”. Not only did they agree about history’s proper subject matter, they were also leading members of a community of historians in late Victorian Britain who sought to promote history’s scientific status against men of letters who were more interested in history’s literary potential. Seeley and Freeman seemed particularly to relish in exposing such historical imposters while promoting their own vision of history as a scientific and autonomous discipline. These similarities aside, the two diverged considerably when reflecting on the posthumous legacy of one such man of letters who likely did more than any other to popularize English history in the nineteenth century. Whereas Seeley believed that Lord Macaulay harmed history’s development by corrupting the general reading public’s historical sensibilities, Freeman argued that historians owed Macaulay a great debt of gratitude for not only basing his narratives on factual accuracy but also for doing so while reaching an extremely large audience. In debating about Macaulay, it is clear that Seeley and Freeman had different conceptions about the normative audience for a professional history.